Faktor – Faktor Yang Berhubungan Dengan Kontaminasi Deterjen Pada Air Minum Isi Ulang Di Depot Air MInum Isi Ulang (DAMIU) Di Kabupaten Kendal Tahun 2009 - Sulistyandari, Hartini; Sulistyani, Sulistyani; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background : People are very depends on mineral water supplies especially for drinks. The results from Central Java Health Laboratory on November 21st 2008 to 95 Mineral Water Refill Depo (DAMIU) at Kendal shows that 85% of the samples examined has Alkyl Benzena sulfonates (ABS) detergent around 0.03 – 0.06 ug/lt. The results shows that the quality of the refillable mineral waters in Kendal were contaminated by detergents. This research was done to examined the factors that correlated with the detergent contaminated to refillable mineral waters at Mineral Water Refill Depo in Kendal. Method : This research is an observational research using surveillance methods and a cross sectional approaches. This research is using a questionnaires which already passed the validity and reliability tests. Primary and secondary datas were examined and analysed using a chi square test method. Result : The results shows that from about 50 DAMIU : 18 DAMIUs (36%) does not have a standardized water supplies, 28 DAMIUs (56%) does not have a standardized equipments, 21 DAMIUSs (42%) does not have a standardized process, 27 DAMIUs (54%) does not have a standardized sanitation, and 30 DAMIUs (60%) were contaminated by detergents. Furthermore, factors that correlated with the detergents contamination on refillable mineral waters at mineral water depo (DAMIU) in Kendal at 2009 are the water supplies (p-value : 0.03), equipment (p-value : 0.01), the process (p-value : 0.001) and sanitation (p-value : 0.027). Conclusion : The suggestion are to the owners of the DAMIUs to have a valid laboratory tests, especially to those correlated with the water supplies, the delivery, the water tank and the preconsumable mineral water, at least every 6 (six) months, using a standardized equipments, having a standard operating procedures (SOP) to operate DAMIUs, do not clean the tank and gallon with soaps or detergents and the needs of routine supervising and surveillance from the Health Department and ASPADA. Keywords : DAMIU, Detergents, Kendal